Penggunaan Media Sosial Instagram terhadap Peningkatan Minat Baca Siswa: Studi Kasus di SMA Negeri 1 Gowa - Malik, Sri Wahyuni; Achmad, Annisa Putri; Ansar, Khairul; Basri, Muh. Bahly (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2022)
This research examines the influence of social media, especially the Instagram account @pramukasalis, on students' reading interest at SMA Negeri 1 Gowa. Reading interest is defined as a strong desire to read, which is influenced by intrinsic and extrinsic factors. Previous research shows that interesting content on social media can increase the reading interest of the younger generation. The method used was descriptive qualitative, with in-depth interviews with four students as participants. The research results show that the use of Instagram contributes positively to increasing students' reading interest. Content presented in an interesting and informative manner encourages students to read more actively. Respondents revealed that clear and straightforward content made them more interested in seeking further information. This research highlights the importance of digital literacy strategies that integrate social media to increase interest in reading, as well as the need to develop effective literacy programs among students. Overall, this research provides insight into how social media can be an effective tool in increasing interest in reading among the younger generation, as well as suggesting the need for a more structured approach in utilizing digital content for educational purposes.